Technical Change and the Measurement of Capital and Output - Diamond, Peter A. (Review of Economic Studies, 1965)
Journal Article Technical Change and the Measurement of Capital and Output Get access Peter A. Diamond Peter A. Diamond University of California, Berkeley, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 4, October 1965, Pages 289–298, https://doi.org/10.2307/2295836 Published: 01 October 1965